Selling your properties to foreigners? - Awang, Adibah (FKSG, UTM, 1997)
Prior to March 25, 1985, there was no restriction as far as origin, race and citizenship went with regard to ownership of land in Malaysia. Pursuantto Act ASS7 of 1984 (hereinafter referred to as "the 1984 Amendment"), Part ThirtyThree (A) was inserted in the National Land Code, the effect of which was to impose restriction on foreign ownership of landed properties. In the case of land subject to the category "agriculture", there was an absolute prohibition on its dealings in favour of foreigners. But in the case of land subject to the category "building", a disposal could be effected in favour of a non-citizen upon the prior written consent of the State Authority. Any acquisition of land in contravention of these provisions shall be null and void. However, land subject to the category "inqu~try:~call b_e acquired freely by the foreigners.